Model Evaluasi Kinerja Pemasok PT XYZ dengan Metode Analytical Hierarchy Process - Triwulandari S. Dewayana; Wahyu S. Dani (UIN Sultan Syarif Kasim Riau, 2016)
The results of the analysis of supplier performance evaluation model PT XYZ show that themodel has the disadvantage of only using two evaluation criteria and performed separately. The weaknesswas led to the management of PT XYZ has a problems in taking decisions related to the performance ofsuppliers. This research aims to design supplier performance evaluation model that is expected to improveefficiency and effectiveness in implementation. The method used is Analytical Hierarchy Process.Structure hierarchical model consists of four levels, namely objectives, criteria, sub-criteria andalternatives. The proportion namely Quality (46%), Delivery (24%), Cost (8%), Response (22%), PACS(45%), warranty Claim (11%), Quality Audit System (44%), kipping, stop line, stop variant (100%), Costdown (100%), the response PACS (44%), the response FTIR (7%), the response Finding Audit (38%), andthe response kipping, stop line, stop variants (11 %). Verify the model shows that the model produces avalue corresponding predetermined assessment standards and can be implemented. Validation of themodel showed that the contents include the evaluation required by the customer; evaluation can beconducted objectively; and sufficiently improve the efficiency and effectiveness in implementation.Keywords: Analytical Hierarchy Process, model, performance evaluation, supplier